1996
DOI: 10.1172/jci118446
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-specific overexpression of phospholamban alters calcium kinetics and resultant cardiomyocyte mechanics in transgenic mice.

Abstract: Phospholamban is the regulator of the cardiac sarcoplasmic reticulum (SR) Ca 2 ϩ -ATPase activity and an important modulator of basal contractility in the heart. To determine whether all the SR Ca 2 ϩ -ATPase enzymes are subject to regulation by phospholamban in vivo, transgenic mice were generated which overexpressed phospholamban in the heart, driven by the cardiac-specific ␣ -myosin heavy chain promoter. Quantitative immunoblotting revealed a twofold increase in the phospholamban protein levels in transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
233
3
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(256 citation statements)
references
References 32 publications
18
233
3
2
Order By: Relevance
“…Both PLB and SLN inhibit SERCA activity in the heart by lowering the apparent calcium affinity of the pump [42,46,47]. The inhibitory effect of SLN is relieved upon β-adrenergic stimulation, as observed for PLB [13,[46][47][48].…”
Section: Sln Functionally Differs From Plbmentioning
confidence: 81%
See 3 more Smart Citations
“…Both PLB and SLN inhibit SERCA activity in the heart by lowering the apparent calcium affinity of the pump [42,46,47]. The inhibitory effect of SLN is relieved upon β-adrenergic stimulation, as observed for PLB [13,[46][47][48].…”
Section: Sln Functionally Differs From Plbmentioning
confidence: 81%
“…On the other hand, over-expression of PLB in the heart resulted in a decrease in SR Ca 2+ uptake and depressed cardiac contractile performance in vivo. [42] These studies revealed that a shift in PLB: SERCA ratio leads to a corresponding shift in SERCA affinity for Ca 2+ , so that an increase in the PLB: SERCA ratio leads to decreased Ca 2+ affinity. Thus, an alteration in the PLB: SERCA ratio can affect SR Ca 2+ transport.…”
Section: Transgenic Approaches To Study the Role Of Plb And Sln In Camentioning
confidence: 98%
See 2 more Smart Citations
“…While such models did not develop any severe phenotype apart from slightly depressed systolic function at similar amounts of overexpression 25,26 , the contractile function in Epac1-PLN mice was slightly but clearly increased (Supplementary Table 1). This discrepancy might be due to the compensatory upregulation of SERCA2a protein expression in our Epac1-PLN mouse model or to the intrinsic properties of the sensor molecule, but not of the overexpressed PLN ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%